Determinants of Organizational Citizenship Behavior: The Case of an Indonesian Insurance Company - Mahir Pradana; Mahendra Fakhri; Alini Gilang; Puti Khairin (Jurnal Bisnis Manajemen, 2018)
A company's human resource aspect can gain benefit from extra-role behaviors known as organizational citizenship behavior (OCB). This research discusses about organizational citizenship behavior (OCB) of the employees at an insurance company based in Jakarta, Indonesia. The purpose of this research to analyze the dominant factors that influence OCB in the company. Factors affecting the OCB are altruism, conscientiousness, sportsmanship, courtesy and civic virtue. The type of research used is descriptive with quantitative method. The respondents were 66 employees of Satria Muda Sucore Agency. The sampling technique using probability sampling with simple random sampling type and using factor analysis method. The results of research showed that OCB is in the decent and more to ‘high’ category. This research formed five factors that are tolerance factor, help behavior factor, compliance factor, participation factor and loyalty factor. Tolerance factor is the most dominant factor of OCB.